Implementasi Penggunaan Model Pembelajaran Team Assisted Individualization (TAI ) pada Pemahaman Siswa Kelas V SD pada Materi Sistem Perncernaan Manusia - Argantini, Renny Yulia Savita; Juniarso, Triman; Wardani, Imas Srinana (Pendagogia: Jurnal Pendidikan Dasar, 2024)
The aim of this research is to see how the TAI (Team Assisted Individualization) type cooperative learning model is implemented in fifth grade elementary school on the subject of the human digestive system. This research uses a qualitative approach with descriptive methods. The subjects in this research were 28 class V students at SDN Tenggilis Mejoyo 1 Surabaya. Data collection was carried out with science subject tests on the human digestive system and followed up with interviews to strengthen the test results. The results show that the application of TAI learning makes it easier for students to work on questions and understand the material. Make students think critically about the test questions that have been given. Firstly, regarding collaboration, many students initially had difficulty understanding science material. However, collaboration in groups helps them because they can help each other and ask questions to each other with group members. Second, they are taught to help each other and work together and be responsible for their duties. Third, students become more motivated by having quizzes and competitions in learning.